Skladenjske konstrukcije med podredjem in priredjem - Smolej, Mojca (Slovenščina 2.0, 2018)
Sentences in the form of subordinate clauses perform numerous syntactic and semantic roles. The number of different forms and roles of subordinate clauses is large but unfortunately not yet fully described. Some subordinate clauses are almost completely ignored in the Slovenian linguistics. On the basis of primary functions, subordinate clauses are divided into four basic groups: a) subordinate clauses that are part of the main clause; b) subordinate clauses that are not part of the semantic knot of the main clause; c) subordinate clauses that are subordinate only on the structural level and are originally not part of the speech; d) subordinate clauses that are subordinate only on the structural level, but perform the role of modifiers of the main clause on the semantic level and are therefore called particle clauses. In this article, we then focus more precisely on subordinate clauses of the third group that do not express any of the foreseen semantic relations; and that is probably one of the reasons why they are almost completely excluded from grammatical treatment. Surely, one of the reasons is also that in the Slovenian grammar the subordinate clauses are often looked at as the clause equivalents of sentence clauses. The understanding of subordinate clauses as sentence clauses was transferred also to primary and high schools but sadly, there has never been a focus or strong emphasis on those subordinate clauses that do not have their own equivalents among expected sentence clauses. Similar are particle subordinate clauses which form coordinate or subordinate syntactic relationships with the pre or after positioned sentence structures only on the formal syntactic level and not on the semantic level. The above written is also one of the main reasons why the Slovenian grammar has not yet included them into its study. The analysis shows that it would be necessary to find all occurrences of subordinate forms in the corpus and define their new syntacticsemantic and pragmatic-communication roles. It would also be necessary to look at all connector means in the corpus and analyse their syntactic, semantic, and broader text roles, and by so doing the syntactic relations should not be confused with semantic ones. A thorough analysis of all forms of subordinate clauses and all connector means could further lead to new theoretical findings. Everything written so far should, along with the analysis of the majority of the written language, also be verified in spoken corpora.
Keywords: contrastive subordinate clauses; členkovni odvisniki; odvisniki; oppositional subordinate clauses; particle clauses; protivni odvisniki; pseudohypotaxis; psevdohipotaksa; Slovene; slovenščina; subordinate clauses